2015
DOI: 10.1097/mcc.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia

Abstract: Experiments involving hypercapnia have covered a wide range of illness models with varying degrees of success. It is becoming evident that deliberate hypercapnia in the clinical setting should seldom be used, except wherever necessitated to avoid ventilator-associated lung injury. A more complete understanding of the molecular mechanisms must be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Interestingly, systemic blood pressures were very similar across the PaCO 2 subgroups in this cohort. PaCO 2 could yet be an important mediator in vascular effects, cardiopulmonary resuscitation and cerebral perfusion [ 13 , 33 ]. In view of that, the association between hypocapnia and mortality may be explained by cerebral vasoconstriction, whereas hypercapnia may be less harmful due to increased peripheral tissue oxygenation [ 34 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, systemic blood pressures were very similar across the PaCO 2 subgroups in this cohort. PaCO 2 could yet be an important mediator in vascular effects, cardiopulmonary resuscitation and cerebral perfusion [ 13 , 33 ]. In view of that, the association between hypocapnia and mortality may be explained by cerebral vasoconstriction, whereas hypercapnia may be less harmful due to increased peripheral tissue oxygenation [ 34 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several years ago, it has been hypothesized that inducing hypercapnia could have been beneficial in patients with acute respiratory failure by attenuating lung inflammation and injury 4 . However, hypercapnia has been associated with impaired alveolar epithelial function, induced immunosuppression, pulmonary hypertension and diaphragmatic dysfunction [5][6][7][8][9][10] . Along these lines, devices allowing extracorporeal CO 2 removal (ECCO2R) to facilitate ultraprotective ventilation have been recently developed [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…HCA also attenuates the inflammatory activation of p42/44 MAP-kinase, an enzyme that has numerous effects on cytoskeletal and focal adhesion proteins that are directly involved in endothelial permeability. 5 , 6 We have shown that airway pressure is synergistic with vascular pressure in altering K f ; 7 thus, the ability of HCA to mitigate alveolar injury during VILI prompted us to hypothesize that HCA may also influence endothelial barrier function during mechanical stress.…”
Section: Introductionmentioning
confidence: 99%